School Health, Nutrition and Education for All Levelling the Playing Field - Jukes, Matthew C. H (CABI, 2014)
This book has benefited from discussions with several colleagues during the writing of a previous chapter on "School-Based Health and Nutrition Programs" in the book Disease Control Priorities in Developing Countries1. We would like to thank Kathleen Beegle, Sheldon Shaeffer, Amaya Gillespie, Seung-hee Frances Lee, Anna-Maria Hoffman, Jack Jones, Arlene Mitchell, Delia Barcelona, Balla Camara, Chuck Golmar, Lorenzo Savioli, Malick Sembene, Tsutomu Takeuchi and Cream Wright for their valuable contributions in this regard. We are very grateful to Criana Connal for comments on drafts of the book and to Dick Murnane for cleaning up our imprecise use of terminology from the field of Economics. We would like to thank Anastasia Said for tireless editing work and to thank both Richard Suswillo at the Partnership for Child Development (PCD) and Sarah Hulbert at CAB International for smoothing the process of manuscript completion.